RESOURCES FOR MUTUAL PERSONAL TRANSFORMATION OF TEACHERS AND FUTURE SPECIALISTS IN THE FIELD OF SUPPORTING PERSONS WITH AUTISM - Suprun , Hanna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article contains a theoretical overview of the concept of personal transformation in its interdisciplinary connections and in the psychological context. The associative connection with close psychological categories: personal development, personal changes, personal growth has been clarified. A working definition of the concept of personal transformation of future specialists accompanying persons with autism during training has been developed. Differences in content were revealed in the evaluation of the level of personal transformation, its features and factors from the point of view of teachers and students during studies at the educational and professional program "Intervention in Autism" of the second (bachelor’s) level of education of the Boris Grinchenko Kyiv Metropolitan University.